Effect of pre-harvest application of growth regulators on yield and quality of elephant- foot yam (Amorphophallus paeoniifolius) during storage (Current Horticulture, 2024)
The effect of pre-harvest application of growth regulators on yield and quality of elephant-foot yam (Amorphophallus paeoniifolius  Dennst.) was studied during storage at Horticultural College and Research Institute, TNAU, Coimbator,e during 2017-18.  Thirteen pre-harvest treatments with cycocel, ethrel and kinetin were used individually and in combination with ridomil at  different concentrations 15 days and 30 days before harvesting. The combination of cycocel @ 500 ppm + ridomil @ 0.5% sprayed  30 days before harvesting recorded highest mean corm weight (820.60 g) and yield 36.70 tonnes/ha. After harvesting, corms  were stored in well-ventilated dry room with relative humidity of 60-75 %. There was a significant loss in corm weight, starch  content, dry matter and oxalate content during storage. The corm weight was significantly higher in T8 (791.60 g), followed by  T11 (773.30 g) and T2 (686.10 g) after 6 months of storage. There was no significant loss in starch and dry-matter content in corms  in all treatments during storage. The starch content ranged from 8.96 to 10.20% and dry-matter content from 21.50 to 25.25%. The  oxalate content was significantly lower in T8 (115.5 mg/100g), followed by T2 (120 mg/100g) and T9 (123 mg/100g).
Keywords: Growth regulators; Corm weight; Starch; Dry matter; Oxalate content